Urgensi Penerapan Omnibus law Untuk Menyelesaikan Permasalahan Pembentukan Regulasi Di Indonesia - Roman Situngkir (Iuris Studia: Jurnal Kajian Hukum, 2022)
The use of omnibus law as a mechanism to overcome regulatory obstacles due to too many (hyper regulation) and overlapping (overlapping) existing regulations. This mechanism is essentially something new and can act as a breakthrough for the reformulation of the preparation of laws and regulations in Indonesia. This research is a normative legal research, so according to the type and nature of the research, the data sources used are secondary data consisting of primary legal materials and secondary legal materials consisting of books, scientific journals, scientific works, and articles that can provide explanations about the law. primary material. The nature of this research is descriptive analytical. As for what is meant by descriptive analytical research is a research that can describe in detail and systematically about the object under study. Primary legal materials are legal materials that bind or make the public understandable, including legal products that are the subject of study and legal products as tools for forming critical law. Secondary legal materials include explanations of primary legal materials in the form of expert doctrine found in books, journals, and websites. The results show that the main characteristic of omnibus law in the United States is that it helps parliamentarians to form consensus. This is because every member of parliament has the right to attach his draft law to the omnibus law. So the application of omnibus law is more of a political style or motive to smooth the passage of a bill into law, while the main characteristic of omnibus law in Turkey is a political motive or style to speed up and shorten the legislative process by using other auxiliary methods. There is no difference in the legislative process between those proposed by the government and those proposed by members of parliament as in Turkey. Then it goes into the extent to which the urgency of implementing the omnibus law in solving the problems of the formation of regulations in Indonesia can be seen that so far there are several problems such as: a) hyper regulation, b) inharmonious regulation and overlapping.